Snap bean planted on living perennial mulch of grass and legume and in tilled soil with organic amendment - de Oliveira, Nelson Geraldo; De-Polli, Helvécio; de Almeida, Dejair Lopes; Guerra, José Guilherme Marinho (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the agronomic performance of snap bean planted on living perennial mulch of bahia grass (Paspalum notatum Flüggé) and of peanut (Arachis pintoi Krapov & Gregory) and in a conventional tillage soil as a control. Different parcels and doses of poultry bed manure (0, 7, 14 and 28 t ha-1) were used in a Planosol soil from August to October of 2002. The statistical design was a split plot, in completely randomized blocks, with four replications, using a quadratic model to analyze the results. Snap bean yield was similar for the tillage system treatments without competition effect from the living mulch, in which direct seeding of the main crop was performed with a hoe. The greatest snap bean yield estimated by regression model was 20.3 t ha-1, corresponding to the dose of 26 t ha-1 of manure applied in parcels. The direct seeding of snap bean on living perennial mulch of bahia grass and perennial peanut is agronomicaly viable, with positive preliminary results on snap bean yield.